Phytochemical profiling of bark of Dalbergia sissoo L. Roxb. Using HPTLC technique - Rajbhoj B G,; S. H. Dive,; J. M. Waghmare, (The Bioscan, 2026)
Dalbergia sissoo Roxb. commonly referred to as Indian Rosewood, is a well-recognized medicinal species belonging to the family Fabaceae. Traditionally, it has been employed in the management of various ailments such as inflammation, pain, diabetes, and microbial infections. The present investigation seeks to establish a chromatographic fingerprint of D. sissoo using High-Performance Thin Layer Chromatography (HPTLC) for qualitative phytochemical profiling and standardization purposes. HPTLC analysis of the plant extract revealed ten distinct, well-resolved peaks with Rf values ranging from 0.01 to 0.82, indicating the presence of a complex array of phytoconstituents. Among these, peak 10 accounted for the maximum area percentage (58.22%), signifying its predominance within the extract. The remaining peaks showed area percentages between 0.40% and 11.95%, corresponding to minor components. Although the individual compounds remain unidentified, the distinctive chromatographic pattern confirms the presence of multiple bioactive constituents in the extract. Keywords Dalbergia sissoo L Roxb. Bark powder, HPTLC.